The Relationship Between The Level Of Maternal Knowledge About Nutritious Food To The Nutritional Status Of Toddlers In The Bamboo Shower Village, Sambas District, Sibolga City In 2019 - Meiyati Simatupang (Science Midwifery, 2019)
Improving the quality of independent human resources needs to be supported by a balanced nutritional situation which must be supported by the availability of sufficient food at a price that is stable and affordable by the purchasing power of the general public. The results of the national census survey revealed that the percentage of under-fives who were malnourished was 71.88% in 2012 and in 2013 it fell to 69.59%. Toddlers with less/bad nutrition were 25.82% in the same year and increased to 28.17% in the following year. This research is descriptive analytic with a cross- sectional approach